2015
DOI: 10.1302/0301-620x.97b2.35154
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of micro-organisms isolated from infected lower limb arthroplasties using high-intensity narrow-spectrum (HINS) light

Abstract: High-intensity narrow-spectrum (HINS) light is a novel violet-blue light inactivation technology which kills bacteria through a photodynamic process, and has been shown to have bactericidal activity against a wide range of species. Specimens from patients with infected hip and knee arthroplasties were collected over a one-year period (1 May 2009 to 30 April 2010). A range of these microbial isolates were tested for sensitivity to HINS-light. During testing, suspensions of the pathogens were exposed to increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
2
14
0
Order By: Relevance
“…It is possible that grouping these organisms has skewed the data, and this may be particularly pertinent with regard to Gram‐negative organisms, as studies have demonstrated high sensitivity of microaerophilic ( Campylobacter , Helicobacter ) and anaerobic ( Fusobacterium ) organisms. For example, C. jejuni required a dose of 18 J cm −2 for >5 log 10 reduction , H. pylori required 10–20 J cm −2 for up to 6 log 10 reduction , and Fusobacterium nucleatum required an average dose of 17.8 J cm −2 for a 1 log 10 reduction , whereas facultatively anaerobic organisms such as Escherichia and Salmonella generally require greater doses of violet‐blue for inactivation, with studies demonstrating as much as 2214 J cm −2 required for a 5 log 10 reduction of E. coli and 739.6 J cm −2 for a 1.4 log 10 reduction of S. enterica serovar enteritidis . Therefore, future reviews could involve in‐depth analysis of these organisms to discover whether sensitivity to violet‐blue light is linked with microbial oxygen requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that grouping these organisms has skewed the data, and this may be particularly pertinent with regard to Gram‐negative organisms, as studies have demonstrated high sensitivity of microaerophilic ( Campylobacter , Helicobacter ) and anaerobic ( Fusobacterium ) organisms. For example, C. jejuni required a dose of 18 J cm −2 for >5 log 10 reduction , H. pylori required 10–20 J cm −2 for up to 6 log 10 reduction , and Fusobacterium nucleatum required an average dose of 17.8 J cm −2 for a 1 log 10 reduction , whereas facultatively anaerobic organisms such as Escherichia and Salmonella generally require greater doses of violet‐blue for inactivation, with studies demonstrating as much as 2214 J cm −2 required for a 5 log 10 reduction of E. coli and 739.6 J cm −2 for a 1.4 log 10 reduction of S. enterica serovar enteritidis . Therefore, future reviews could involve in‐depth analysis of these organisms to discover whether sensitivity to violet‐blue light is linked with microbial oxygen requirements.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Haughton et al (2012) inactivated Campylobacter jejuni using 395 nm light, while Bumah et al (14,15) demonstrated the antimicrobial efficacy of 470 nm light against Salmonella enterica and S. aureus. Additionally, a small number of bacterial endospores, fungi and yeasts have been inactivated using violet-blue light (16)(17)(18)(19)(20)(21)(22)(23). To date, little is known about viral susceptibility; however, there is now published evidence demonstrating 405 nm light inactivation of a viral surrogate, bacteriophage ɸC31, and a mammalian virus, feline calicivirus, without the requirement of additional photosensitizers (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a panel of microbial isolates from cases of infected joint arthroplasty were tested (Gupta et al, 2015), including 39 isolates of Gram-positive bacteria ( S. aureus, S. epidermidis, E. faecalis, S. pneumoniae , Corynebacterium striatum , Coagulase negative Staphylococcus , etc), 11 isolates of Gram-negative bacteria ( E. coli, K. pneumoniae, P. aeruginosa , and Serratia marcescens ) and one isolate of C. albicans . aBL was emitted from a high-intensity narrow-spectrum light at 405 nm.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…21,22 The majority of the publications on aBL have been confined to in vitro efficacy studies. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] There have been only three published reports to demonstrate the efficacy of aBL for infections in vivo. [39][40][41] It has been demonstrated that aBL (415-nm) significantly reduced the bacterial burden (both Gram-positive and Gram-negative) in mouse wounds or burns, [39][40][41] and was protective in a lethal mouse model of P. aeruginosa infection.…”
Section: Introductionmentioning
confidence: 99%